IoT-based Single-Phase Power Factor and Control Panel Monitoring System - Subrata, Arsyad Cahya; Perdana, Muhammad Sukmadika; Ariyansyah, Qolil (The Indonesian Institute of Science and Technology Research, 2023)
The power factor is a value obtained by comparing the actual power value and apparent power in an electric circuit. Because it is related to the quality of the distributed power, this power factor needs to be monitored. Devices with inductive loads generally cause power factor distortion, causing losses. Power factor monitoring is carried out periodically to ensure the efficiency of electricity distribution to the building. Power factor monitoring is usually done on the control panel of a building by measuring the voltage and current flowing. Manual monitoring could be more ineffective in terms of time and effort and has the potential for recording errors. This study proposes a power factor monitoring system on the control panel to facilitate recording. The system created is integrated with IoT technology so that it can monitor and record automatically anywhere and anytime. The developed system has an error percentage of 1.53% for the voltage sensor and 5.02% for the current sensor.